Sustainability assessment for Small and Medium Enterprise (SMEs) by using fuzzy logic approach: a direction and further research - Mahmood, Salwa; Hassan, Mohd Fahrul; Hemdi, Abdul Rahman; Kafuku, John Mbogo; Mat Saman, Muhamad Zameri (Penerbit UTHM, 2021)
Sustainability assessment have been studied by several researchers focusing to determine set of criteria on case studies selected. However, only few studies have been done on assessing the sustainability of SMEs in Malaysia. Although there are several studies on sustainability assessment for manufacturing company in Malaysia, they do not provide a comprehensive study that including all Triple Bottom Line (TBL) perspectives. To fill this gap, this study will propose a comprehensive framework for assessing sustainability among SMEs that including all TBL perspectives, which is covering environmental, economy and social aspects in sustainability assessment. Primary and secondary data will be used in this study. For primary data, Delphi study will be conducted to obtain the reliable data. Next, fuzzy inference system (FIS) will be applied in this study as methodology for integrating collected data. As for secondary data, literature review from previous current research work will be summarize for comparison purpose. This study is expected to guide SMEs towards sustainability as well as increase awareness hence to promote a serious path towards a more sustainable business model. In regards, Malaysia Government can monitor the sustainability level among SMEs which is have linked with the Malaysia regulations.